Effect of aluminium hydroxide loading on the compression stress and modulus, thermal conductivity and acoustic properties of palm-based polyurethane hybrid composite - Nor Rabbi’atul ‘Adawiyah Norzali; Khairiah Hj Badri; Mohd Zaki Nuawi (Universiti Kebangsaan Malaysia, 2011)
The effect of adding aluminum hydroxide (ATH) in the palm-based polyurethane hybrid composite was studied. The compression stress and modulus, thermal conductivity and acoustic property were determined. The hybrid composite was prepared by adding 10 wt% of oil palm empty fruit bunch fibre (EFB) followed by ATH at varying amount of 2, 4 and 6 wt% of the overall mass of the resin. The compression stress and modulus gave the highest values of 575 kPa and 2301 kPa, respectively at 2 wt% ATH. At 4 wt% ATH, the compression stress and modulus decreased to 431 kPa and 1659 kPa, respectively and further decreased at 6 wt% ATH to 339 kPa and 1468 kPa respectively. The k-value increased with the increment of the ATH loading exhibited a poor thermal conductivity. Sound absorption analysis indicated that the absorption coefficient was higher at higher frequency (4000 Hz) for all samples with PU-EFB/ATH with 4% ATH showed the highest absorption coefficient.